The counsellor’s perception of attention to student diversity in secondary education - Mirian Miranda Morais; Joaquín Lorenzo Burguera Condon; José Miguel Arias Blanco (INFAD, 2014)
This investigation arises from the need to explore a variety of experiences aimed at meeting the demands of diversity in Secondary Education, identify those aspects promoting and hindering inclusive practices. This research has been made using a descriptive and exploratory methodology (both qualitative and quantitative), including a questionnaire made up of 55 items (Likert scale) and open questions. Experts were also interviewed, gathering a sample of 51 public high school counsellors in Asturias. Results show that, even though schools apply a consolidated set of measures to cater for diversity, there are still legal limitations and a lack of resources to provide suitable answers to the educational needs of our students. Attention to student diversity is present when it comes to make decisions at an organizational and operational level or to create and develop plans and programmes. Regarding the teaching practice, it is obvious that teachers are aware of the importance of meeting the needs of diversity in the classroom; however, there is still a long way to go as far as methodological approaches and teacher training are concerned.